Impact of a Checklist on Clinic Flow and Patient Visit Times at a Student-Run Free Clinic - Alyssa Scott; Dolly Patel; Alexa Hughes; Alexis Reedy-Cooper (Journal of Student-Run Clinics, 2021)
Background: While student-run free clinics are a valuable resource to the community, there are limitations leading to challenges with clinic flow. Previous research has identified checklists as a useful intervention in medicine. This project sought to evaluate the efficacy of a checklist on student volunteer accuracy and adherence to clinic flow, and patient visit times.Methods: From June 2019 to February 2020, volunteers at select clinics received a checklist listing important steps of a patient encounter. The authors sent surveys to volunteers following all clinics and recorded patient visit times. The outcomes measured were: volunteer accuracy (number of steps completed); volunteer adherence (order of steps); perceived helpfulness of the checklist; and patient visit times. The first three outcomes were assessed via self-reported survey data and the last outcome was assessed via collection of time data. Fisherâ€™s exact tests to assess statistical significance (p<0.05).Results: Thirty-eight student volunteers completed surveys, for a response rate of 67.9%. Eighteen (47%) of those who completed surveys were part of the experimental group (received checklist), while the remaining 53% were part of the control group (did not receive checklist). Nine (50%) of 18 volunteers with a checklist spoke to patient navigation and/or lifestyle educators before presenting to an attending, compared to 1 (5%) of 20 volunteers without checklist (p=0.0025). Of the 18 volunteers who received a checklist, 16 (89%) found the checklist helpful.  There was no significant difference between mean visit time pre-checklist (74 minutes, SD= 29.6) and post-checklist (79 minutes; SD=28.3; p=0.46, n=134).Conclusion: The checklist improved clinic flow by increasing volunteer accuracy and adherence. The checklist was also perceived to be helpful, and did not increase patient visit times.